Lewis Henry Morgan's comparisons : reassessing terminology, anarchy and worldview in Indigenous societies of America, Australia and Highland Middle India - Pfeffer, Georg, 1943- (Berghahn Books, 2019)
"About 150 years ago L.H. Morgan compared relationship terminologies, societal forms, and ideas of property to recognize the interdependence of the three domains. From a new perspective, the book will re-examine, confirm and criticize, Morgan's findings to conclude that reciprocal affinal relations determine most 'classificatory' terminologies and regulate many non-state societies, their property notions, and their rituals. Apart from references to American and Australian features, such holistic socio-cultural constructs will be exemplified by elaborate descriptions of little-known contemporary Indigenous societies in highland Middle India, altogether comprising many millions of members"--